Physical, Chemical, and Sensory Characteristics of Chicken Sausage with Analog Meat Substitution - Herlina, Herlina; Aji, Satriya Bayu; Purnomo, Bambang Herry (Department of Agro-industrial Technology, University of Brawijaya, 2021)
AbstractThis research was conducted to make chicken sausage substitution using analog meat from gluten, soy protein isolate, wheat flour, Anjasmoro soybean, and gembili tuber flour to reduce chicken meat used and produce sausages with the same quality. The purpose of this study was to determine the sausage’s physical, chemical, and sensory properties. The formulation of chicken sausage with analog meat substitution used a completely randomized design method with a single factor (chicken meat and analog meat ratio), with five treatments and each treatment was repeated three times. The five treatments are P1 = 90% chicken meat : 10% analog meat, P2 = 80% chicken meat : 20% analog meat, P3 = 70% chicken meat : 30% analog meat, P4 = 60% chicken meat : 40% analog meat and P5 = 50% chicken : 50% analog meat. The results showed that the substitution of chicken meat with analog meat had a significant effect on the physical, chemical, and sensory properties of chicken sausage. The results show that 70% chicken meat and 30% analog meat is the best treatment.Keywords: analog meat, chicken sausage, substitution AbstrakPenelitian ini dilakukan untuk membuat substitusi sosis daging ayam menggunakan daging analog dari gluten, isolat protein kedelai, tepung terigu, kedelai Anjasmoro dan tepung umbi gembili. Sehingga dapat mengurangi penggunaan daging ayam dan dapat menghasilkan sosis dengan kualitas yang sama. Tujuan dari penelitian ini adalah untuk menentukan sifat fisik, kimia dan sensorik sosis. Formulasi pembuatan sosis daging ayam dengan substitusi daging analog, menggunakan metode rancangan acak lengkap dengan faktor tunggal (rasio penambahan daging ayam dan daging analog) dengan lima perlakuan serta masing - masing perlakuan diulang tiga kali ulangan. Lima perlakuan tersebut ialah P1 = 90% daging ayam : 10% daging analog, P2 = 80% daging ayam : 20% daging analog, P3 = 70% daging ayam : 30% daging analog, P4 = 60% daging ayam : 40% daging analog dan P5 = 50% daging ayam : 50% daging analog. Hasil penelitian menunjukkan bahwa susbtitusi daging ayam dengan daging analog berpengaruh nyata terhadap sifat fisik, kimia, dan sensorik sosis ayam. Hasil penelitian menunjukkan bahwa perlakuan70% daging ayam dan 30% daging analog adalah perlakuan terbaik.Kata Kunci: daging analog, sosis daging ayam, substitusi